2020
DOI: 10.3390/molecules25112687
|View full text |Cite
|
Sign up to set email alerts
|

Cyperus articulatus L. (Cyperaceae) Rhizome Essential Oil Causes Cell Cycle Arrest in the G2/M Phase and Cell Death in HepG2 Cells and Inhibits the Development of Tumors in a Xenograft Model

Abstract: Cyperus articulatus L. (Cyperaceae), popularly known in Brazil as “priprioca” or “piriprioca”, is a tropical and subtropical plant used in popular medical practices to treat many diseases, including cancer. In this study, C. articulatus rhizome essential oil (EO), collected from the Brazilian Amazon rainforest, was addressed in relation to its chemical composition, induction of cell death in vitro and inhibition of tumor development in vivo, using human hepatocellular carcinoma HepG2 cells as a cell model. EO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…After the appearance of tumor with a 3 mm 3 volume, all tumor-bearing mice were enrolled randomly into subgroups (5 mice per group) and COE (20, 40, and 80 mg/kg) or saline were administered through a gastric tube every day until the end of the experiment ( Qian et al, 2012 ). During the experiment, the length (L), width (W) and height (H) of tumors were measured with a caliper; tumor mass was calculated according to the previous report ( Nogueira et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…After the appearance of tumor with a 3 mm 3 volume, all tumor-bearing mice were enrolled randomly into subgroups (5 mice per group) and COE (20, 40, and 80 mg/kg) or saline were administered through a gastric tube every day until the end of the experiment ( Qian et al, 2012 ). During the experiment, the length (L), width (W) and height (H) of tumors were measured with a caliper; tumor mass was calculated according to the previous report ( Nogueira et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the in vitro trial Aristolone contained therein has an antiproliferative effect on the LoVo cell line with IC50 16.60 mg/ml. Aristolone stated as cytotoxic/anticancer potential (Ahmad, 2016), (Nogueira, 2020). Aristolone in this trial was found as much as 11.3%.…”
Section: Resultsmentioning
confidence: 57%
“…Animals were grafted subcutaneously with HepG2 cells (10 7 cells per 500 μL), in the left armpit and randomly divided into four groups: (G1) vehicle‐treated mice (5 % DMSO, n= 20); (G2) 5‐FU‐treated mice (10 mg/kg, n =10); (G3) EO‐treated mice (40 mg/kg, n =10); and (G4) EO‐treated mice (80 mg/kg, n =10). These doses were based on previous studies with EO [33–37] . Starting one day after tumor implantation, the animals were treated intraperitoneally for 21 consecutive days.…”
Section: Methodsmentioning
confidence: 99%